Woke, Inc. : inside corporate America's social justice scam - Ramaswamy, Vivek (New York : Center Street, 2023)
"There's a new invisible force at work in our economic and cultural lives. It affects every advertisement we see and every product we buy, from our morning coffee to a new pair of shoes. "Stakeholder capitalism" makes rosy promises of a better, more diverse, environmentally-friendly world, but in reality this ideology championed by America's business and political leaders robs us of our money, our voice, and our identity. Vivek Ramaswamy is a traitor to his class. He's founded multibillion-dollar enterprises, led a biotech company as CEO, he became a hedge fund partner in his 20s, trained as a scientist at Harvard and a lawyer at Yale, and grew up the child of immigrants in a small town in Ohio. Now he takes us behind the scenes into corporate boardrooms and five-star conferences, into Ivy League classrooms and secretive nonprofits, to reveal the defining scam of our century. The modern woke-industrial complex divides us as a people. By mixing morality with consumerism, America's elites prey on our innermost insecurities about who we really are. They sell us cheap social causes and skin-deep identities to satisfy our hunger for a cause and our search for meaning, at a moment when we as Americans lack both. This book not only rips back the curtain on the new corporatist agenda, it offers a better way forward. America's elites may want to sort us into demographic boxes, but we don't have to stay there. Woke, Inc. begins as a critique of stakeholder capitalism and ends with an exploration of what it means to be an American in 2021--a journey that begins with cynicism and ends with hope." -- Inside front jacket flap.
Introduction: The woke-industrial complex -- The Goldman rule -- How I became a capitalist -- What's the purpose of a corporation? -- The rise of the managerial class -- The ESG bubble -- An arranged marriage -- Henchman of the woke-industrial complex -- When dictators become stakeholders -- The silicon leviathan -- Wokeness is like a religion -- Actually, wokeness is literally a religion -- Critical diversity theory -- Woke consumerism and the big sort -- The bastardization of service -- Who are we?
Keywords: Corporations -- Moral and ethical aspects; Capitalism -- Moral and ethical aspects; Business and politics; Corporations -- Political aspects; Consumption (Economics) -- Moral and ethical aspects; Social justice; Corporate culture